PERAN TOKOH ADAT DALAM MEMPERKUAT PARTISIPASI PEMUDA PADA PENGELOLAAN LUBUK LARANGAN DI KOTA PADANGSIDIMPUAN - Imelda Sari Daulay; Sudirman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the challenges of modernization and the busy schedules of youth, which threaten the sustainability of Lubuk Larangan management as a form of local wisdom in Padangsidimpuan City. To address this issue, this study aims to describe the role of customary leaders (tokoh adat) in strengthening youth participation and to identify the forms of youth involvement in its management. A descriptive qualitative method was employed, with subjects selected through purposive sampling, consisting of one customary leader, one active youth, and one less active youth. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman interactive model. The results indicate that customary leaders play a crucial role as mentors, motivators, social supervisors, and preservationists of customary values, which are proven to increase the awareness and responsibility of the younger generation. Youth participation itself is concretely demonstrated through their involvement in deliberations (musyawarah), community mutual cooperation (gotong royong), monitoring the Lubuk Larangan area, and the collective harvest agenda. Despite facing obstacles from the current of modernization, the active role of customary leaders remains a key factor in maintaining the sustainability of this traditional management.